Red-emission molecular rotors for ultrafast and wash-free imaging mitochondria viscosity in cells and tissues. (6th March 2023) - Yu, Kun; Shen, Shuting; Wang, Yaxuan; Yang, Jing; Wang, Zhiyu; Ding, Feiyang; Ge, Jiayi; Deng, Yi; Hu, Lei; Wang, Meifang; Wang, Hui
Graphical abstract: Abstract: Mitochondrial viscosity is an important parameter in biological system, of which the abnormality is related to a variety of diseases. Therefore, it is necessary to develop fluorescent probes for imaging mitochondrial viscosity. Herein, two red-emission fluorophores (L1 and L2 ) with donor–π–bridge-acceptor (D-π-A) structure were facilely synthesized and systematically studied. These fluorophores were demonstrated to be viscosity-sensitive, and particularly, L2 could precisely target mitochondria through a wash-free procedure. Moreover, probe L2 was membrane potential-independent, and it was capable of permeating the cell membrane within a short time (≤30 s). Importantly, L2 was workable in fresh tissues with a favorable penetration depth of 33.89 µm. All these excellent performances endow probe L2 promising capability to investigate the correlation between mitochondrial viscosity and related diseases.